Knowledge Sharing in Software Development - (:unkn) unknown (Springer Nature Switzerland, 2024)
Knowledge is the most important resource in the field of software development, the success of which is based on the exchange of knowledge among the team members of the software development project. The aim of this research is to provide a catalogue of li...
Keywords: Gestión del conocimiento; Desarrollo de software